Serdexmethylphenidate/dexmethylphenidate for children with attention-deficit/hyperactivity disorder: dose optimization from a laboratory classroom study - Andrew J. Cutler; Andrew J. Cutler; Scott H. Kollins; Scott H. Kollins; Matthew N. Brams; Meg Corliss; Charles Oh; Rene Braeckman; Ann C. Childress (Frontiers in Psychiatry, 2024)
ObjectiveTo evaluate treatment responder rate using the Attention-Deficit/Hyperactivity Disorder Rating Scale-5 (ADHD-RS-5) score based on optimized dose level of serdexmethylphenidate/dexmethylphenidate (SDX/d-MPH) and changes in ADHD severity in children (aged 6–12 years) with ADHD.MethodsDuring a 21-day dose-optimization phase, 155 patients initiated treatment with 39.2/7.8 mg SDX/d-MPH in the first week and then were titrated to an optimum dose; 5 patients were downtitrated to 26.1/5.2 mg, 76 were uptitrated to 52.3/10.4 mg, and 69 remained at 39.2/7.8 mg during the following 2 weeks. Responder threshold values were 30% and 50% based on the percent change from baseline (day 0) to days 7, 14, and 21 in the ADHD-RS-5 score. The Conners 3rd Edition-Parent score was used to assess weekly changes in ADHD severity during the dose-optimization and treatment phases.ResultsOf the 5 subjects whose dose was optimized at 26.1/5.2 mg, ≥80% across all days had ≥50% responder rate. Of the 69 subjects whose dose was optimized at 39.2/7.8 mg, 81.2% had ≥50% responder rate by day 21. Of the 76 subjects whose dose was optimized to 52.3/10.4 mg, 72.4% had ≥50% responder rate by day 21. Changes in ADHD severity, based on mean Conners 3rd Edition-Parent scores, improved from baseline at each visit during dose optimization for each subscale. At the dose-optimization phase, Conners 3rd Edition-Parent scores improved from baseline for SDX/d-MPH in all subscales.ConclusionA high percentage of subjects were responders upon reaching their final optimized dose. SDX/d-MPH demonstrated significant reductions in ADHD severity in children based on the Conners 3rd Edition-Parent scores. Determining the optimal dosage of SDX/d-MPH and its effect on ADHD severity could enable the development of a more clinically relevant treatment regimen in children with ADHD.